EFEKTIFITAS TERAPI MURROTAL AL-QUR’AN DALAM PERAWATAN PASIEN KRITIS: INTEGRATIVE REVIEW - Rustam, Junaidy Suparman (Ensiklopedia of Journal, 2021)
The intervention of the Holy Qur’an recitation can be defined as an ancient and widely used intervention to recover from sickness and promote good health. The sound of the pleasant rhythm of the Holy Qur’an recitation which can be served as a spiritual music. Based on the literature showed that the Holy Qur’an recitation with a beautiful voice and best quality was appropriate to use in caring critically ill patients. This study aimed to identify the utilization of the Holy Quran recitation interventions and its effectiveness in critically ill patients. An integrative literature search was conducted using several databases supplemented with a hand-search of journals there were published in the year 2011 to 2021. The searching strategies based on PICO questions that included all English articles and  used keywords for searching including the Holy Quran recitation, voice of the Holy Quran recitation, critically ill patients, critical care . All of these keywords were mixed in different combinations. Several studies showed that the Holy Qur’an recitation has holistic effects in various population. Nevertheless, there are still limited studies to identify the effectiveness of the Holy Qur’an recitation in caring critically ill patients.